2005
DOI: 10.1113/jphysiol.2004.077735
|View full text |Cite
|
Sign up to set email alerts
|

Cellular sources, targets and actions of constitutive nitric oxide in the magnocellular neurosecretory system of the rat

Abstract: Nitric oxide (NO) is a key activity-dependent modulator of the magnocellular neurosecretory system (MNS) during conditions of high hormonal demand. In addition, recent studies support the presence of a functional consitutive NO tone. The aim of this study was to identify the cellular sources, targets, signalling mechanisms and functional relevance of constitutive NO production within the supraoptic nucleus (SON). Direct visualization of intracellular NO, along with neuronal nitric oxide synthase (nNOS) and cGM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
46
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 82 publications
6
46
1
Order By: Relevance
“…It is becoming clear that basal NO production can play a variety of roles in regulating functions of neuronal circuits. For example, in supraoptic nucleus, NO tone generated by magnocellular neurons exerts inhibitory control over oxytocin and vasopressin systems (Stern and Zhang, 2005). During late pregnancy, nNOS mRNA is reduced and endogenous NO production markedly down-regulated, facilitating oxytocin release during parturition (Srisawat et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It is becoming clear that basal NO production can play a variety of roles in regulating functions of neuronal circuits. For example, in supraoptic nucleus, NO tone generated by magnocellular neurons exerts inhibitory control over oxytocin and vasopressin systems (Stern and Zhang, 2005). During late pregnancy, nNOS mRNA is reduced and endogenous NO production markedly down-regulated, facilitating oxytocin release during parturition (Srisawat et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…NO has been described as an activity-dependent modulator of the magnocellular neurosecretory system. We and others have shown that NO signaling is required for stimulated VP release from SON tissue punches (Gillard et al, 2007) and the latter serves to regulate MNC electrical activity and pituitary VP output (Kadowaki et al, 1994;Liu et al, 1998;Stern and Ludwig, 2001;Stern and Zhang, 2005). Moreover, nNOS expression and NOS activity (as assessed by NADPH-d) in MNCs appears to be responsive to physiological state, suggesting an activity-dependent role for NO signaling in the control of body water and salt balance.…”
Section: Introductionmentioning
confidence: 81%
“…Evidence also exists for NO involvement in the neurotoxic actions of organohalogens such as polybrominated diphenyl ethers (PBDEs). NO functions in both normal and pathological CNS processes associated with endocrine, homeostatic as well as synaptic functions (Dawson and Dawson, 1996;Garthwaite and Boulton, 1995;Stern and Zhang, 2005). There is evidence that most of the dual actions of NO may be targets of PCBs.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by recent studies indicating that inhibitors of nitric oxide synthase (NOS) activity within the PVN results in sympathoexcitation and increased blood pressure (76). Moreover, diminished basal NO availability within the PVN has been shown to contribute to elevated neurohumoral drive in pathological conditions such as hypertension, heart failure and diabetes (16,73,78).Accumulating evidence indicates that NO effects on neuroendocrine and autonomic outputs from the SON and PVN are mediated by inhibition of the electrical activity of both magnocellular (3,37,59,62) and preautonomic neurons (34, 35), respectively, and that these actions are mediated through an enhancement of GABAergic transmission (33,35,71). One of the classical mechanisms underlying NO signaling in neurons involves activation of soluble guanylyl cyclase (31).…”
mentioning
confidence: 99%
“…Accumulating evidence indicates that NO effects on neuroendocrine and autonomic outputs from the SON and PVN are mediated by inhibition of the electrical activity of both magnocellular (3,37,59,62) and preautonomic neurons (34, 35), respectively, and that these actions are mediated through an enhancement of GABAergic transmission (33,35,71). One of the classical mechanisms underlying NO signaling in neurons involves activation of soluble guanylyl cyclase (31).…”
mentioning
confidence: 99%